The structure and behavior of Pakistan's imports from selected Asian countries: An application of gravity model - Summaira Malik; Amatul R. Chaudhary (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
This paper critically analyzes Pakistan's import policy during 1990s and explores the determinants of bilateral import flows between Pakistan and selected Asian countries (SAC) in recent past. Much research on international trade patterns focuses on primitive causes of trade such as differences in national factor endowments, preferences and technologies but we have focused on macroeconomic determinants to overcome the problems of trade deficit. It contains the policy issues which may be helpful for policy makers of other developing countries facing same conditions. A gravity model of international trade is empirically tested with the help of generalized least square (GLS) method of estimation for panel data. Empirical results reveal that income, exchange rate and openness of SAC economies are contributing factor of Pakistan's import flows. There is convincing evidence that current import flows are positively correlated with previous year whereas infrastructural bottlenecks have negative impact on Pakistan's import flows.
Keywords: 330; Behavior of Imports; Pakistan; Gravity Model; Import; Asien; Außenhandelsstruktur; Außenhandelselastizität; Gravitationsmodell; Pakistan